The Perception of Audiences Towards Dialog Harmoni program on TV Al-Hijrah As A Medium of Interfaith Dialogue in Malaysia - Mazhisham, Panji Hidayat (Universiti Sains Islam Malaysia, 2016)
The aim of this study is to investigate the perceptions of audiences towards the “Dialog Harmoni” program on TV Al-Hijrah as a medium of interfaith dialogue in Malaysia. This study involved 290 respondents from various races and religions who have already watched the Dialog Harmoni program. The sample was drawn randomly. The instrument of this study is a quantitative means, using a questionnaire containing of 55 items related to the audiences’ perceptions towards Dialog Harmoni program. The questionnaire is based on four key dimensions, namely dimension of the importance of Dialog Harmoni, the roles of Dialog Harmoni, the moderator and panelists, and its contents. Descriptive analysis was used to find the frequency, percentage, mean and standard deviation. Data was analysed using Statistical Package of Social Sciences (SPSS) for Windows version 20.0. Cronbach alpha reliability coefficient for the instrument was α = .849. The result shows that the overall perceptions of the viewer towards Dialog Harmoni program on TV Al-Hijrah as a medium of interfaith dialogue was at a high level (mean = 3.90). While the mean level of the audiences’ perception of the dimension of the importance in Dialog Harmoni (mean = 4.09), the dimension of the role in Dialog Harmoni (mean = 3.90), the dimensions of the moderator and panelists in Dialog Harmoni (mean = 3.87) and the dimensions of the contents in Dialog Harmoni (mean = 3.73). The implication of this study is that the Dialog Harmoni program should be continued because it has positive impacts on the society of all races and religions in Malaysia. In addition, Dialog Harmoni program can be used as a medium of interfaith dialogue which can attract young people to learn and gain knowledge about the diversity of religious beliefs, practices, customs and traditions of other religions in Malaysia.